Redefining atrial fibrillation treatment success: patient-defined goals for arrhythmia burden and health-related quality of life - Alexander E. Kolomaya; Brian Zenger; Michael Torre; Andrew Redd; T. Jared Bunch; Trudie Lobban; Morgan M. Millar; Jonathan P. Piccini; John A. Spertus; Rachel Hess; Benjamin A. Steinberg (Critical Pathways in Cardiology: A Journal of Evidence-Based Medicine, 2026)
Background: Despite the use of atrial fibrillation (AF) cutoff of 30s as the standard for success in most AF clinical trials, patients consider an AF Severity Scale (AFSS) of ≤ 5 or AF duration ≤ 1 hour as treatment success. Prevalence and factors associated with these patient-defined endpoints are unknown. Methods: We performed a cross-sectional analysis using a single-site cohort of AF patients. We report rates of patient-defined treatment success (AFSS ≤ 5 or AF burden ≤ 1 hour) and multivariable analyses to identify factors associated with either successful outcome. Results: From 2019 to 2023, 2087 patients had available AFSS symptom scores and 2305 had ambulatory ECG monitoring. Of these, 862 (41%) had AFSS scores ≤5 and 1130 (49%) had AF burden ≤1 hour. After adjusted analysis, older age (OR 1.03, 95% CI 1.02-1.04, p